In vitro gas production and rumen fermentation profile of fresh and ensiled genetically modified high–metabolizable energy ryegrass - Winichayakul S; Beechey-Gradwell Z; Muetzel S; Molano G; Crowther T; Lewis S; Xue H; Burke J; Bryan G; Roberts NJ (FASS Inc. and Elsevier Inc. on behalf of the American Dairy Science Association, 2020)
We previously generated a high–metabolizable energy (HME) perennial ryegrass (Lolium perenne) by genetically modifying the plant to increase the leaf lipid content. Although substantial progress has been made toward characterizing physiological changes of HME ryegrass, very limited information exists for feeding value and its suitability for adoption into the pastoral system. In this study, independent HME ryegrass lines with a range of elevated leaf lipid concentrations were analyzed for changes in fatty acids and possible associated changes in the broader nutritional profile, including the gross energy, which was found to increase by 6.8%. Because ryegrass is often ensiled and fermentation in the rumen leads to biohydrogenation of fatty acids as well as enteric methane production, we sought to investigate these effects on HME ryegrass. This was achieved by performing mini-scale silos and using an automated gas measurement system to incubate the material in rumen fluid in vitro for 24 h. Our study included treatments comprising 3 independent HME ryegrass genotypes and wild-type control materials prepared fresh and as silage, employing in total 5 incubation studies, using rumen fluids collected from 4 nonlactating Jersey × Holstein cows. At intervals during the incubation, the production of gases, volatile fatty acids, and the degree of biohydrogenation were measured. Statistical data analysis indicated that differences in the nutritional compositions of the ensiled materials largely reflected those of their fresh counterparts. Incubation of both fresh and ensiled HME ryegrass in rumen fluid resulted in: (1) a greater percentage of valuable unsaturated fatty acids compared with the control; (2) a significant reduction of butyrate; and (3) a 10 to 15% decrease in the methane proportion of the total gas production. We conclude that ensiling could be a convenient option for preserving HME as a locally produced high-value supplementary feed; however, large-scale application needs to be investigated. In this paper we discuss the potential use of HME ryegrass to enhancing forage feeding value and the potential environmental benefits to the pastoral agriculture industry.
Keywords: cysteine-oleosin; high–metabolizable energy ryegrass; methane production; rumen fermentation; Animals; Butyrates; Cattle; Digestion; Energy Metabolism; Fatty Acids, Volatile; Female; Fermentation; Lolium; Methane; Plants, Genetically Modified; Rumen; Silage